Helicobacter pylori CagA disrupts pancreatic epithelial barrier integrity - Romero-Fabela, Anais; Silva-Olivares, Angelica; Chacon, Melisa; Rendon-Huerta, Erika P.; Betanzos, Abigail (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe oncoprotein CagA is the major virulence factor of Helicobacter pylori and plays a central role in the development of gastric disorders. H. pylori CagA+ infection has been implicated with an increased risk of developing extragastric diseases such as pancreatic cancer; however, the mechanisms remain unclear.MethodsIn this study, BxPC-3 pancreatic epithelial cells were infected with H. pylori bacterial strains CagA+ (26695 and PMSS1) or CagA− (Tx30a).ResultsInfection with CagA+ strains resulted in a significant disruption of epithelial barrier integrity, as demonstrated by transepithelial electrical resistance assays. Western blot and immunofluorescence analyses revealed altered expression and cytoplasmic relocalization of key apical junctional complex proteins. Meanwhile, claudin-4 and occludin levels increased, that of ZO-1 remained unchanged, and those of E-cadherin and β-catenin decreased. Likewise, cytoskeletal rearrangements were observed, particularly the loss of the actin apical ring and mislocalization of actin-binding proteins, such as cortactin and vinculin, at the cell borders. The loss of barrier integrity and cytoskeletal alterations were associated with morphological changes and increased cell motility, as demonstrated by wound healing assays. In addition, infection was accompanied by an increase in IL- 8 secretion.DiscussionThese findings suggest that CagA alters the pancreatic epithelial cells’ functions. Therefore, CagA represents an undescribed risk factor in the pathogenesis of H. pylori-associated pancreatic illness.